Pendampingan/Revitalisasi Posyandu Cempaka 1 Banjar Taked Desa Selulung Kecamatan Kintamani - Ni Wayan Sri Ekayanti; Putu Ayunda Trisnia (Warmadewa Minesterium Medical Journal, 2024)
Stunting is chronic malnutrition, especially experienced by toddlers, and has unfavorable short-term and long-term outcomes. There are so many impacts caused by stunting that require serious treatment, both in Indonesia and throughout the world. Stunting can have an impact on cognitive decline, impaired immunity, and the risk of suffering from degenerative diseases in the future. The main causes of stunting include family factors/parenting patterns, breast milk, inadequate provision of MPASI, and infection. This community service activity involves families of stunted and potentially stunted toddlers in Banjar Taked, Selulung Village, Kintamani, and Bangli as partners. The main focus of the problems is increasing family knowledge regarding making and providing adequate, healthy, and nutritious MPASI from local food ingredients, as well as increasing the ability of posyandu cadres to carry out anthropometric measurements. The proposed solution to the problem of insufficient nutritional intake in children under five is increasing the knowledge of mothers of toddlers about parenting patterns and healthy food for children under five and the skills in making PMT from local food ingredients as well as increasing the ability of posyandu cadres in carrying out anthropometric measurements. The methods used in this activity are counseling, discussion, and training. The results of this activity are an increase in the knowledge of posyandu cadres in carrying out anthropometric measurements as well as an increase in the knowledge of mothers of toddlers regarding providing MPASI that is adequate and has high nutritional value. After this service was carried out, partners began to be moved to provide nutritious food to prevent stunting in toddlers.